Comics for oral health education: construction, validation, and analysis of efficacy - Haad Ruiz da Silva, Jefter; Sant’Ana Honorato, Eduardo Jorge; Ferreira Regalado, Diego; da Silva Carvalho, Érica; Ferreira Barcelar Junior, Francisco; Ruiz da Silva, Iracema; Xavier Monteiro, Ângela (O Mundo da Saúde, 2022)
Illustrated media has been a widely used device for oral health education, with comics being a format that is still under explored in terms of validation and analysis of their effectiveness towards the target audience. This study aimed to evaluate the effectiveness of a comic book in the process of oral health education to children between 6 and 12 years of age attended at the pediatric dentistry clinic of a dental polyclinic in the Brazilian Amazon. A playful-educational comic book was made, validated, and incorporated into a kit containing 01 toothbrush, 01 floss, and 01 toothpaste. Subsequently, a questionnaire was applied with the parents (N=50), before and after the delivery of the kits, which evaluated the child’s oral hygiene care and the impressions on the impact of the comics on the oral hygiene of their children. The results were analyzed descriptively, through absolute frequencies and percentages using the McNemar test (p<0.05). There was an increase of 55.32% of the children who started flossing after methodological implementation. It was also found that there was no statistical difference between the frequency of brushing after delivery of the kit (p=0.873), but there was a significant increase in the frequency of flossing among the children evaluated (p=0.0401). The comics were statistically effective in increasing the frequency of flossing, with comic books having a good acceptance of both children and parents.